Rubens, painter of sketches - Rubens, Peter Paul (Museum Boijmans Van Beuningen, 2018)
Of the nearly 500 oil sketches executed by Rubens over the course of his career, this exhibition includes 73 loaned from leading institutions world-wide, including the Louvre, the Hermitage, the National Gallery and the Metropolitan Museum, and also from the collections of the Prado and the Boijmans (which have two of the largest holdings of this type). On display for four months in Room C of the Jerónimos Building, the sketches are shown alongside a number of prints, drawings and paintings by Rubens which provide a context for them, bringing the total number of works on display to 93.00Exhibition: Museo Nacional del Prado, Madrid, Spain (10.04.-05.08.2018) / Museum Boijmans van Beuningen, Rotterdam, Netherlands (08.09.2018-13.01.2019)